Cobalt ions induce metabolic stress in synovial fibroblasts and secretion of cytokines/chemokines that may be diagnostic markers for adverse local tissue reactions to hip implants. (1st September 2021) - Eltit, Felipe; Noble, Jake; Sharma, Manju; Benam, Niloufar; Haegert, Anne; Bell, Robert H.; Simon, Felipe; Duncan, Clive P.; Garbuz, Donald S.; Greidanus, Nelson V.; Masri, Bassam A.; Ng, Tony L.; et al.
Abstract: Adverse local tissue reactions (ALTRs) are a prominent cause of hip implant failure. ALTRs are characterized by aseptic necrosis and leukocyte infiltration of synovial tissue. The prevalence of ALTRs in hips with failing metal implants, with highest rates occurring in patients with metal-on-metal articulations, suggests a role for CoCrMo corrosion in ALTR formation. Although hypersensitivity reactions are the most accepted etiology, the precise cellular mechanism driving ALTR pathogenesis remains enigmatic. Here we show that cobalt ions released by failing hip implants induce mitochondrial stress and cytokine secretion by synovial fibroblasts: the presumptive initiators of ALTR pathogenesis. We found that in-vitro treatment of synovial fibroblasts with cobalt, but not chromium, generated gene expression changes indicative of hypoxia and mitophagy responses also observed in ALTRs biopsies. Inflammatory factors secreted by cobalt-exposed synovial fibroblasts were among those most concentrated in ALTR synovial fluid. Furthermore, both conditioned media from cobalt-exposed synovial fibroblasts, and synovial fluid from ALTRs patients, elicit endothelial activation and monocyte migration. Finally, we identify the IL16/CTACK ratio in synovial fluid as a possible diagnostic marker of ALTRs. Our results provide evidence suggesting that metal ions induce cell stress in synovial fibroblasts that promote an inflammatory response consistent with initiating ALTR formation. Statement of significance: We demonstrate that the cytotoxic effects of cobalt ions on the synovial cells (fibroblast) is sufficient to trigger inflammation on hip joints with metal implants. Cobalt ions affect mitochondrial function, leading to the auto phagocytosis of mitochondria and trigger a hypoxic response. The cell's hypoxic response includes secretion of cytokines that are capable of trigger inflammation by activating blood vessels and enhancing leukocyte migration. Among the secreted cytokines is IL-16, which is highly concentrated in the synovial fluid of the patients with adverse local tissue reactions and could be use as diagnostic marker. In conclusion we define the cells of the hip joint as key players in triggering the adverse reactions to hip implants and providing biomarkers for early diagnosis of adverse reactions to hip implants. Graphical abstract: Image, graphical abstract